2019
DOI: 10.3390/su11051293
|View full text |Cite
|
Sign up to set email alerts
|

Service-Oriented Load Balancing Approach to Alleviating Peak-Hour Congestion in a Metro Network Based on Multi-Path Accessibility

Abstract: To further improve the service quality and reduce safety risks in current congested metro systems during peak hours, this paper presents a load balancing (LB) approach so that available capacity can be utilized more effectively in order to alleviate peak hour congestion. A set of under-utilized yet effective alternative routes were searched using a deletion algorithm (DA) in order to share the passenger loads on overcrowded metro line segments. An optimization model was constructed based on an improved route g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Thus, it is more reliable to measure accessibility for each transport mode as a separate unit [26]. Deep analyses have also been done on what aspects of accessibility people have via a given means of transport, such as the train, the bus, the automobile, and the taxi [27][28][29][30]. A technique that incorporates data from current geographic information systems for the purpose of offering a real-time measurement of the accessibility and connectivity of transport modes is described in [31,32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is more reliable to measure accessibility for each transport mode as a separate unit [26]. Deep analyses have also been done on what aspects of accessibility people have via a given means of transport, such as the train, the bus, the automobile, and the taxi [27][28][29][30]. A technique that incorporates data from current geographic information systems for the purpose of offering a real-time measurement of the accessibility and connectivity of transport modes is described in [31,32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model determined the service offset and turn-back stations. Huang et al [11] constructed a load balancing approach to optimize metro train operation. The model was based on an improved route which generalized the time utility function, considering the penalties of both in-vehicle congestion and transfers, thereby improving the service quality and reducing safety risks in metro systems, at the same time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different paths will bring flow pressure on different stations, and thus the inter-OD traffic is often allocated to efficient paths by means of passenger flow allocation. Huang found that the crowd can be relieved by sharing the passengers to the alternative routes [15]. Peng et al divided the passenger flow into different types and created a dynamic assignment model to reflect the real passenger flow state [16].…”
Section: Introductionmentioning
confidence: 99%